Thomas & friends. Hero of the rails - Allcroft, Britt; Awdry, W.; Gullane Limited; HIT Entertainment ([New York] : Hit Entertainment ; Santa Monica, Calif. : Distributed by Lionsgate, 2009)
Follow Thomas as he discovers Hiro, an abandoned engine from a faraway land. Fearing that Hiro will be scrapped, Thomas enlists the help of many friends, but mishaps, mistakes, and one boastful engine could foil their rescue plans.
Full screen.
Created for televsion by Britt Allcroft.
Based on The railway series by The Reverend W. Awdry.
Bonus features : "Thomas & Spencer" racing game ; "Who's pulling into the station?" game ; "Go, go Thomas" karaoke music video ; Thomas & friends bedroom makeover.
Not rated.
DVD; Dolby Digital 5.1 and 2.0.
Keywords: Thomas the Tank Engine (Fictitious character) -- Juvenile drama; Locomotives -- Juvenile drama; Children's television programs; Animated television programs; Television programs for the hearing impaired